Implementasi Data Terpadu Kesejahteraan Sosial (DTKS) Di Desa Pangkalan Baru Kecamatan Siak Hulu Kabupaten Kampar - Dwi Herlinda; Elly Nielwaty; Meylina Elsi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
The implementation of social welfare policies requires accurate and up-to-date databases so that social assistance can be distributed appropriately. The Integrated Social Welfare Data (DTKS) plays a strategic role as national master data in determining the targets of social protection programs. This study aims to analyze the implementation of DTKS management in Pangkalan Baru Village, Siak Hulu Subdistrict, Kampar Regency, using George C. Edward III's policy implementation model, which covers the aspects of communication, resources, disposition, and bureaucratic structure. The study uses a qualitative approach with a descriptive method. Research informants were determined purposively, including village officials, the DTKS verification team from the Kampar Regency Social Service, and Beneficiary Families (KPM). Data collection techniques were carried out through in-depth interviews and documentation, while data analysis used the stages of data reduction, data presentation, and conclusion drawing. The results showed that the implementation of DTKS in Pangkalan Baru Village had been carried out in accordance with national guidelines and had a clear bureaucratic structure. However, its implementation still faced obstacles in the form of limited human resources, information technology facilities, and a multi-level and relatively slow bureaucratic process. These conditions have an impact on data updates that are not yet fully optimal and have the potential to affect the accuracy of social assistance targets. Therefore, it is necessary to strengthen the capacity of village officials, improve cross-sector coordination, and optimize digital systems to support more effective, accurate, and sustainable DTKS management.